ILO And Legal Protection For Indonesian Migrant Workers (Study Case: Adelina) - Nasrullah, Nasrullah; Farman, Logi; Pangestu, Rian Ade; Putra, Ardi Novasela (Universitas Negeri Gorontalo, 2023)
Adelina's case indicates that there are still arbitrary actions experienced by indonesian workers in Malaysia. Adelina is an illegal migrant worker and was convicted of attempted murder by her employer in Malaysia. Adelina often received violent treatment from her employer until Adelina died. This research aims to find the facts of Adelina's case objectively so that it can be an evaluation of the applicable legal formulation. The legal research used is normative legal research, researchers put the law as a building system of norms. Doctrinal legal research in this study uses a regulatory approach, and research sources that are in accordance with the legal issues studied. The results found that the lack of prevention efforts by Indonesia and Malaysia against cases of smuggling of illegal workers resulted in trafficking in persons being the main factor in the occurrence of unlawful acts committed by employers against migrant workers.